Deformity of Nose in Unilateral Clefts - Masood II Khan; R. N. Sharma (Indian Journal of Plastic Surgery)
The cause of the nasal deformity is the hypoplasia or agenesis of the maxilla and nothing else. If the primary cause, is treated first, the patient will have a normal nose. The other deformities are the sequelae of the primary cause that need correction later on.